Tool-supported continuous business process innovation: a case study in globally distributed software teams. (2017) - Heredia, Alberto; Colomo-Palacios, Ricardo; Soto-Acosta, Pedro
During the production of software, individuals acquire tacit knowledge that can be useful to improve business processes. Even though people are geographically dispersed, social software supports the creation of knowledge clusters and provides additional channels to share knowledge for business process improvement. This paper describes a successful case study in which useful tacit knowledge is captured from a knowledge cluster with the aim of innovating services provided by a consultancy organisation. To this end, a knowledge-management-based framework helps to capture useful tacit knowledge, from individuals in different locations by using two social software tools during the production of software. Findings reveal that the use of this framework empowers the continuous innovation of business processes, thus allowing consultancy organisations to provide high-quality solutions. Moreover, the framework allows newcomers to receive support from other colleagues and also mitigates the knowledge loss produced owing to the high rotation of personnel in such organisations.